Eating disorder during the SARS-CoV-2 pandemic - Huete Cordova, Maria Antonieta (2022)
Patients with eating disorder (ED) are a vulnerable population in the context of the COVID-19 pandemic. Some studies describe its negative effect on ED patients and their caregivers. This article presents a narrative review of the impact of the SARS-CoV-2 pandemic on these patients. Depressive and anxious symptoms, risk of self-harm and suicide are identified. Early intervention and management of patients with ED is a great challenge to the continuity of treatment, detection of comorbidities and relapse prevention.